TEACHING METHOD FOR PRIMARY SCHOOL (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article defines teaching methods, offers eight typical teaching styles used by primary school instructors, and discusses the advantages of knowing a variety of approaches